Passive Immunization with Phospho-Tau Antibodies Reduces Tau Pathology and Functional Deficits in Two Distinct Mouse Tauopathy Models - Sankaranarayanan, Sethu; Barten, Donna M.; Vana, Laurel; Devidze, Nino; Yang, Ling; Cadelina, Gregory; Hoque, Nina; DeCarr, Lynn; Keenan, Stefanie; Lin, Alan; Cao, Yang; Snyder, Bradley; et al. (PloS one, 2015)
In Alzheimer's disease (AD), an extensive accumulation of extracellular amyloid plaques and intraneuronal tau tangles, along with neuronal loss, is evident in distinct brain regions. Staging of tau pathology by postmortem analysis of AD subjects suggests a sequence of initiation and subsequent spread of neurofibrillary tau tangles along defined brain anatomical pathways. Further, the severity of cognitive deficits correlates with the degree and extent of tau pathology. In this study, we demonstrate that phospho-tau (p-tau) antibodies, PHF6 and PHF13, can prevent the induction of tau pathology in primary neuron cultures. The impact of passive immunotherapy on the formation and spread of tau pathology, as well as functional deficits, was subsequently evaluated with these antibodies in two distinct transgenic mouse tauopathy models. The rTg4510 transgenic mouse is characterized by inducible over-expression of P301L mutant tau, and exhibits robust age-dependent brain tau pathology. Systemic treatment with PHF6 and PHF13 from 3 to 6 months of age led to a significant decline in brain and CSF p-tau levels. In a second model, injection of preformed tau fibrils (PFFs) comprised of recombinant tau protein encompassing the microtubule-repeat domains into the cortex and hippocampus of young P301S mutant tau over-expressing mice (PS19) led to robust tau pathology on the ipsilateral side with evidence of spread to distant sites, including the contralateral hippocampus and bilateral entorhinal cortex 4 weeks post-injection. Systemic treatment with PHF13 led to a significant decline in the spread of tau pathology in this model. The reduction in tau species after p-tau antibody treatment was associated with an improvement in novel-object recognition memory test in both models. These studies provide evidence supporting the use of tau immunotherapy as a potential treatment option for AD and other tauopathies.